2015
DOI: 10.1097/ajp.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spinal Cord Stimulation on Sensory Characteristics

Abstract: The results support existing evidence suggesting that SCS does not change sensory characteristics, which is important information for both patients and clinicians. Changes in pain intensity after deactivation of SCS may be different in short-term and long-term SCS treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(74 citation statements)
references
References 32 publications
0
60
1
1
Order By: Relevance
“…Fourteen studies included in this review used quantitative sensory testing (QST) to assess the mechanistic effects of SCS (Table ). Thirteen studies used static QST to measure the effects of SCS on a patient's sensory‐detection threshold (first noticeable sensation), pain threshold (first noticeable pain sensation), and/or tolerance (no longer able to withstand the pain sensation) to heat, cold, pressure, tactile, vibratory, or electrical stimuli . An early study by Lindblom and Meyerson found elevations in tactile and vibration perception thresholds in five out of ten patients following SCS .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen studies included in this review used quantitative sensory testing (QST) to assess the mechanistic effects of SCS (Table ). Thirteen studies used static QST to measure the effects of SCS on a patient's sensory‐detection threshold (first noticeable sensation), pain threshold (first noticeable pain sensation), and/or tolerance (no longer able to withstand the pain sensation) to heat, cold, pressure, tactile, vibratory, or electrical stimuli . An early study by Lindblom and Meyerson found elevations in tactile and vibration perception thresholds in five out of ten patients following SCS .…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Campbell et al observed nonsignificant differences in QST measures (e.g., heat‐pain threshold, pressure‐pain threshold, and cold‐pressor tolerance) at baseline, during the SCS trial phase, and one and three months following permanent SCS implantation . Meier et al used similar measures (tactile detection and pain threshold, pressure‐pain threshold, vibration‐detection threshold, heat detection and pain threshold, and cold‐pain threshold) to examine 14 patients (five CRPS patients and nine patients with peripheral nerve injury) with long‐term SCS treatment and found no significant change in sensory characteristics and pain intensity with SCS ON vs. SCS OFF . In a large long‐term study examining the effects of SCS on CRPS patients, Kemler et al found that SCS neither reduced painful sensory symptoms nor decreased heat or cold hyperalgesia .…”
Section: Resultsmentioning
confidence: 99%
“…). Of these, 15 were articles (Table ) and 14 were abstracts/records of ongoing or unpublished studies (Supporting Information Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Seven articles (47%) evaluated vibration detection threshold (Vibration‐DT) in a body region with chronic pain. Five (50 patients overall) noted no change in this threshold under tonic SCS using a Rydel‐Seiffer tuning fork , a vibrator (Somedic, Hörby, Skåne, Sweden) or a biothesiometer (Bio‐Medical Instr., Chagrin Falls, OH, USA) . However, Eisenberg et al reported a significant increase in Vibration‐DT using Medoc's VSA 3000 (Ramat Ishay, Israel) in their patient population (seven FBSS and six CRPS).…”
Section: Resultsmentioning
confidence: 99%
“…Temperature detection thresholds did not differ between patients with SCS and controls in a larger study of patients with CRPS, and only a mild effect on mechanical hyperalgesia was detected . Some have observed changes in temperature discrimination, temporal summation to a painful tonic thermal stimulus, and thermal pain, whereas others have not . Detection and pain thresholds to electrical stimulation were increased in patients implanted chronically compared with those receiving short‐term stimulation .…”
Section: Conventional Waveformsmentioning
confidence: 92%